Toxic Positivity vs. Anxiety: A Critical Discourse Analysis of Emotional Hegemony in Inside Out 2 - Aulfa Reyza Ayuni Prestika; Dery Purnama Saefudin; Siti Nurani; Rita Karmila Sari (Journal of English Language Learning, 2026)
The increasing prevalence of adolescent anxiety and the growing influence of toxic positivity in digital culture have intensified scholarly interest in how emotions are represented and regulated in contemporary society. While previous studies on Inside Out have primarily examined emotional development from psychological and educational perspectives, the discursive struggle between competing emotional narratives remains underexplored. This study aims to investigate the linguistic strategies employed by Joy and Anxiety, analyze their discourse struggle within Headquarters, and explain how this conflict reflects contemporary adolescent mental health experiences. Employing a qualitative approach, the study analyzes the script of Inside Out 2 using Norman Fairclough’s three-dimensional Critical Discourse Analysis framework, encompassing text, discourse practice, and sociocultural practice. The findings reveal that Joy and Anxiety construct emotional authority through contrasting discursive strategies: Joy promotes optimism, certainty, and emotional control, whereas Anxiety emphasizes vigilance, anticipation, and future-oriented concerns. Their interaction constitutes a struggle for discursive dominance over Riley’s identity formation and decision-making processes. Furthermore, this conflict mirrors broader sociocultural pressures experienced by adolescents, including social media visibility, performance-oriented expectations, and the normalization of emotional self-regulation. The study contributes to Critical Discourse Analysis by conceptualizing emotions as competing forms of emotional hegemony and offers insights for media literacy and adolescent mental health education.